2022
DOI: 10.1111/cpr.13357
|View full text |Cite
|
Sign up to set email alerts
|

Additional Cover

Abstract: The cover image is based on the Original Article Tetrahedral framework nucleic acids promote diabetic wound healing via the Wnt signalling pathway by Zejing Wang et al., https://doi.org/10.1111/cpr.13316.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…[33,34] These findings may explain why even naked tFNAs itself could enhance proliferation in many pathological conditions. [35][36][37] Given that efficient unloading of miRNAs from tFNAs is a crucial step to ensure the downstream biological functions, we demonstrated that the expression of miR-21 in HCECs significantly increased after T-21 treatment compared to control groups. This mainly attributes to the existence of RNase H, an endonuclease widely presents in mammalian cells which degrades the RNA strands of heterozygous RNA/DNA molecules while keeps single-stranded or double-stranded RNA molecules intact.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…[33,34] These findings may explain why even naked tFNAs itself could enhance proliferation in many pathological conditions. [35][36][37] Given that efficient unloading of miRNAs from tFNAs is a crucial step to ensure the downstream biological functions, we demonstrated that the expression of miR-21 in HCECs significantly increased after T-21 treatment compared to control groups. This mainly attributes to the existence of RNase H, an endonuclease widely presents in mammalian cells which degrades the RNA strands of heterozygous RNA/DNA molecules while keeps single-stranded or double-stranded RNA molecules intact.…”
Section: Discussionmentioning
confidence: 87%
“…[ 33,34 ] These findings may explain why even naked tFNAs itself could enhance proliferation in many pathological conditions. [ 35–37 ]…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37] The 3.5% agarose gel electrophoresis (Figure 5C) also demonstrated that NTH consists of four ssDNA molecules. [38][39][40] By dynamic light scattering (DSL), the diameter of the NTH was measured uniformly as 13.54 nm (Figure 5D). In Figure 5E and Figure S8, Supporting Information, we illustrate that NTH exhibits a better support effect on the electrode surface than single-stranded aptamers by comparing their current values when detecting the target.…”
Section: Electrochemical Measurement Of Pd-l1mentioning
confidence: 99%